Method for precisely regulating and controlling electron mobility and conductivity of SnO2 nanocrystal in large range through P-type doping

Through P-type doped SnO2 nanocrystals, low-valent metal cations are used to replace high-valent cations in SnO2 to form electron acceptors, solving the problem of mismatch in mobility between electron transport layer and hole transport layer, achieving the balance between electrons and holes, and improving the performance and stability of optoelectronic devices.

CN120548007APending Publication Date: 2025-08-26GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510739611.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

In quantum dot light-emitting diodes and perovskite thin-film solar cells, there are huge differences in carrier mobility and conductivity of the inorganic electron transport layer and organic hole transport layer, resulting in unbalanced electron and hole transport, affecting device efficiency and lifetime.

Method used

Through the P-type doping strategy, low-valent metal cations are used to replace high-valent cations in SnO2 nanocrystals, form electron acceptors, reduce electron concentration and regulate electron mobility and conductivity, and achieve equilibrium with organic hole transport materials.

Benefits of technology

The balance between electron and hole transmission is achieved, and the performance and stability of optoelectronic devices are improved, especially the efficiency and life of quantum dot light-emitting diodes and perovskite thin-film solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120548007A_ABST
    Figure CN120548007A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, in particular to a method for precisely regulating and controlling the electron mobility and conductivity of SnO2 nanocrystals in a large range through P-type doping, which comprises the following steps: (1) replacing tetravalent Sn4 + ions with low-valence metal ions to form P-type doping and form electron acceptors in nanocrystals; (2) through P-type doping, accurate regulation and control on the electron mobility and the conductivity of the SnO2 nanocrystal are realized; and (3) the SnO2 nanocrystalline thin film with the conductivity and mobility being precisely adjustable in a large range is used as an electron transport layer, and is matched with organic hole transport layers with different hole mobility and conductivity, the electron transport layer is applied to the field of photoelectric devices such as quantum dot light emitting diodes and perovskite thin film solar cells, the electron and hole transport balance is realized, and the photoelectric device performance is improved. And the performance and the stability of the semiconductor photoelectric devices are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new material technology, specifically a method for accurately controlling the electron mobility and conductivity of SnO2 nanocrystals over a large range by P-type doping. 4+ ions, realizing P-type doping to form electron acceptors, and then by changing the concentration of P-type doped metal ions, a wide range of precise control of the electron mobility and conductivity of the N-type SnO2 nanocrystal electron transport layer can be achieved. Background Art

[0002] In optoelectronic devices such as quantum dot light-emitting diodes and perovskite thin-film solar cells, a PiN device structure is usually used. The i-layer with high intrinsic resistance is usually composed of a core quantum dot light-emitting layer or a narrow-bandgap perovskite light-absorbing layer. Since these functional layers are thin films with high intrinsic resistance, wide-bandgap P-type hole transport layers and N-type electron transport layers are required on both sides of the film to complete the injection or extraction of holes and electrons. At present, due to the presence of serious deep-level oxygen vacancy defects in wide-bandgap P-type inorganic transport layer materials such as NiO, CuGaO2 and CuCrO2, the device performance is poor. Therefore, the organic P-type hole transport materials widely used in high-performance quantum dot light-emitting diodes and perovskite thin-film solar cell devices include 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt(4,4'-N-4-butylphenyl))] (TFB), poly[bis(4-butyl)-bis(phenyl)benzidine] (poly-TPD), polytriarylamine (PTAA), 2,2',7,7'-tetrakis(N,N-di-p-methoxyaniline)-9,9'-spirobifluorene (Spiro-OMeTAD) and poly(9-vinylcarbazole) (PVK). The mobility of these common hole transport materials ranges from 10 -4 to 10 -6 cm 2 V -1 s -1 The most commonly used electron transport materials are inorganic metal oxide nanocrystal electron transport materials, including wide-bandgap ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystal films, whose electron mobility is as high as 10 -3 cm 2 V -1 s -1The difference in mobility between the two is 1-3 orders of magnitude. Since the electron mobility and conductivity of the electron transport layer of inorganic ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystals are much higher than the commonly used organic hole transport materials mentioned above, there is a serious imbalance in the electron and hole transport in optoelectronic devices such as quantum dot light-emitting diodes and perovskite thin-film solar cells, which reduces the photoelectric conversion efficiency of these optoelectronic devices and damages the stability of the devices. In order to solve the problem of electron and hole transport imbalance caused by the mismatch in the mobility of the electron transport layer and the hole transport layer, the most commonly used method is to dope the organic hole transport material with organic small molecules and oxidize it, thereby improving the hole mobility and conductivity of the organic hole transport layer, making it close to the electron mobility and conductivity of the electron transport layer of inorganic ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystals, and then obtaining a relatively balanced electron and hole transport. For example, in perovskite solar cells, Spiro-OMeTAD or PTAA needs to be doped with small molecules and oxidized to reduce its conductivity from 10 -8 S cm -1 Increase to 10 -4 S cm -1 , while the hole mobility increases from 10 -5 cm 2 V -1 s -1 Increase to 10 -4 cm 2 V -1 s -1 , bringing it close to the electron mobility and conductivity of TiO2 nanocrystal and SnO2 nanocrystal electron transport layers, thereby obtaining high-efficiency perovskite thin-film batteries. Although the hole mobility and conductivity of the organic hole transport layer can be improved by small molecule doping and oxidation, the stability of the organic hole transport material after small molecule doping and oxidation will be greatly reduced, which will seriously damage the stability and service life of the optoelectronic device.

[0003] In addition, by significantly reducing the electron mobility and conductivity of the inorganic electron transport layers of ZnO nanocrystals, TiO2 nanocrystals, and SnO2 nanocrystals, and combining them with undoped organic hole transport materials, it is theoretically possible to achieve a balanced electron and hole transport, thereby obtaining highly efficient optoelectronic devices. Therefore, how to significantly reduce the electron mobility and conductivity of the inorganic electron transport layers of ZnO nanocrystals, TiO2 nanocrystals, and SnO2 nanocrystals, and achieve precise control of the electron mobility and conductivity of the inorganic electron transport layers over a wide range, is a very important and unresolved problem, and research in this area is almost nonexistent. Summary of the Invention

[0004] The present invention aims to solve the problem that in existing quantum dot light-emitting diodes and perovskite solar cell devices, there is a huge difference in carrier mobility and conductivity between the inorganic electron transport layer and the organic hole transport layer. The difference in mobility and conductivity between the two is 1-3 orders of magnitude, resulting in serious imbalance in electron and hole transport, which in turn affects the efficiency and life of the device. The present invention provides a method for accurately regulating the electron mobility and conductivity of SnO2 nanocrystals over a large range through P-type doping.

[0005] Through theoretical analysis and density functional theory (DFT) calculations, we innovatively proposed a P-type doping strategy, using low-valent metal cations to replace high-valent cations in the inorganic electron transport layer of ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystals to form electron acceptors, thereby reducing the electron carrier concentration in N-type ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystals, thereby reducing their electrical conductivity. According to theoretical calculations, when low-valent metal cations replace high-valent cations in ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystals, as the total defect concentration increases, lattice distortion and impurity scattering will become more serious, thereby reducing the electron mobility of ZnO nanocrystals, TiO2 nanocrystals and SnO2 nanocrystal films. Therefore, by changing the concentration of P-type doped low-valent metal cations, we can achieve a wide range of precise control of the conductivity and mobility of the electron transport layer of inorganic metal oxide nanocrystals. By combining them with organic hole transport materials with low hole mobility and low conductivity, we can also achieve the balance of electron and hole transport in quantum dot light-emitting diodes and perovskite thin-film solar cell optoelectronic devices, and ultimately obtain high-performance and stable optoelectronic devices. Since the Zn ion in ZnO nanocrystals is +2 valent, the only low-valent metal cations that can be selected are monovalent Ag. + 、Cu + He Li + Due to the difference in chemical activity, these three monovalent metal ions replace Zn in ZnO nanocrystals. 2+ The lattice position of ions is very difficult, and there is a self-compensation effect in ZnO. Even if these metal ions can be doped into ZnO nanocrystals, they cannot form effective electron acceptors. In addition, the Ti ions in TiO2 nanocrystals are +4 valence, and metal cations with +2 and +3 valence can be doped. There are many types, but due to Mg 2 + 、Zn 2+ 、Ga 3+ 、In 3+ Low-valent metal cations and Ti 4+The huge difference in chemical activity of ions and the high formation energy of substitution defects make P-type doping very difficult. Therefore, we focus on SnO2 nanocrystals, because the Sn ions in SnO2 nanocrystals are +4 valence, and Mg can be doped. 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Low-valent metal cations such as Sn form P-type doping to provide electron acceptors. In addition, these low-valent metal ions 4+ The chemical activity and ionic radius of ions are very similar, so the preparation of Mg 2 + 、Zn 2+ 、Ga 3+ 、In 3+ Ion doping, replacing Sn in SnO2 nanocrystals 4+ ions, forming P-type doping, providing electron acceptors, and then reducing the conductivity and electron mobility of SnO2 nanocrystals, which has extremely high theoretical and experimental feasibility.

[0006] In order to solve the technical problems of the above-mentioned P-type doped SnO2 nanocrystals, the technical solution of the present invention is as follows: A method for accurately controlling the electron mobility and conductivity of SnO2 nanocrystals over a large range by P-type doping, comprising the following steps:

[0007] (1) Using organic acids and organic amines as organic ligands to control the nucleation and growth rates of SnO2 nanocrystals;

[0008] (2) Using organic acids and organic amines to gradually release water at high temperatures, catalyzing and promoting the gradual hydrolysis of tin tetrachloride or tin dichloride to form SnO2 nanocrystals;

[0009] (3) Add Mg to the reaction precursor solution 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion precursor, Mg is prepared by high temperature reaction 2 + 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystals can achieve precise control of the electrical conductivity and electron mobility of SnO2 nanocrystals over a wide range by changing the concentration of doped metal ions;

[0010] (4) Prepared alcohol-soluble or oil-soluble Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+Ion-doped SnO2 nanocrystals are dispersed in water, ethanol, toluene or toluene, and MgO is prepared by solution film forming methods such as spin coating, inkjet printing, screen printing, Czochralski method, slit spraying, and doctor blade coating. 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystalline films with precisely tunable electron mobility and conductivity over a wide range;

[0011] (5) Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystalline films with widely adjustable conductivity and electron mobility are used as electron transport layers, and are paired with organic hole transport layer materials with different hole mobilities and conductivities. They are applied to optoelectronic devices such as quantum dot light-emitting diodes and perovskite thin-film solar cells to achieve a balanced transmission of electrons and holes, thereby improving the performance and stability of these semiconductor optoelectronic devices.

[0012] The organic acid and organic amine at least include one or more of the following organic acids and organic amines, organic acids or organic amines with a carbon chain length ranging from 1 carbon to 18 carbons, and the organic acids are formic acid, acetic acid, propionic acid, acrylic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, isooctanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, stearic acid, oleic acid, linoleic acid, benzoic acid, phenylphosphoric acid, benzenesulfonic acid, citric acid, ascorbic acid, ethylenediaminetetraacetic acid, glycolic acid, oxalic acid, gluconic acid, lactic acid, acrylic acid, salicylic acid, tartaric acid, taurine, glycine, glutamic acid, The organic amine is one or more of methylamine, ethylamine, propylamine, butylamine, tert-butylamine, pentylamine, hexylamine, heptylamine, octylamine, isooctylamine, decylamine, dodecylamine, tetradecylamine, octadecylamine, oleylamine, aniline, benzylamine, ethanolamine, diethanolamine, triethanolamine, dibutylamine, diethylamine, pyridine, propanolamine, isopropanolamine, diisopropanolamine, 2-amino-1-butanol, 2-amino-1,3-propylene glycol, 2-amino-2-methyl-1-propanol, diglycolamine, and polyethyleneimine.

[0013] The high temperature reaction includes 30 degrees to 300 degrees, and the heating methods include normal pressure heating and high pressure autoclave heating.

[0014] The P-type doping ions include but are not limited to Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ One or more of the ions, with a molar doping concentration ranging from 0.01-50%.

[0015] The solution film forming method includes spin coating, inkjet printing, screen printing, pulling method, slit spraying, and blade coating.

[0016] The field of optoelectronic devices includes, but is not limited to, quantum dot light emitting diodes and perovskite thin film solar cells, including upright and inverted device structures.

[0017] The electron mobility and conductivity of the nanocrystalline film can be precisely controlled over a wide range by changing the concentration of doped metal ions. -3 S cm -1 to 10 -8 S cm -1 , the electron mobility of SnO2 nanocrystalline film increases from 10 -2 cm 2 V -1 s -1 to 10 -6 cm 2 V -1 s -1 Precisely adjustable within a wide range.

[0018] The Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ The ion-doped SnO2 nanocrystalline film is used as the electron transport layer, and the organic hole transport layer materials with different hole mobility and conductivity are matched therewith. The photoelectric device is a quantum dot light emitting diode or a perovskite thin film solar cell.

[0019] The photoelectric device is a quantum dot light emitting diode, and its device structure includes an ITO transparent conductive substrate, an electron transport layer, a quantum dot light emitting layer and a hole transport layer.

[0020] The photoelectric device is a perovskite thin film solar cell, and its device structure includes an ITO or FTO transparent conductive glass substrate, an electron transport layer, a perovskite light absorption layer and a hole transport layer.

[0021] The Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+Ion-doped SnO2 nanocrystalline films are used as electron transport layers in optoelectronic devices such as quantum dot light-emitting diodes and perovskite thin-film solar cells. They are paired with commonly used organic hole transport materials with different hole mobilities and conductivity, including 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt(4,4'-(N-(4-butylphenyl))] (TFB), poly[bis(4-butyl)-bis(phenyl)benzidine] (poly-TPD), polytriarylamine (PTAA), 2,2',7,7'-tetrakis(N,N-di-p-methoxyaniline)-9,9'-spirobifluorene (Spiro-OMeTAD), and poly(9-vinylcarbazole) (PVK). The hole mobility of these hole transport materials can be increased from 10 -4 to 10 -6 cm 2 V -1 s -1 The electron and hole transmission balance is achieved by reducing them in sequence, thereby improving the performance and stability of these semiconductor optoelectronic devices.

[0022] The outstanding advantages of the present invention are:

[0023] 1. Use organic acid / organic amine as organic ligand at the same time, they can not only coordinate Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ 、Sn 4+ ions, reduce the activity of the reaction precursors, slow down the nucleation and growth rate of nanocrystals, and at the same time, organic acid and organic amine ligands can also coordinate and complex with the surface metal cations and oxygen anions of the generated SnO2 nanocrystals, slow down the growth rate of nanocrystals, passivate the oxygen vacancy defects on the surface of nanocrystals, and then control the nucleation and growth kinetics of nanocrystals to prepare ultra-small and uniformly sized Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystals;

[0024] 2. Organic acids and organic amines gradually release water through acid-base reactions at high temperatures, which in turn triggers the hydrolysis of tin tetrachloride or tin dichloride. The nucleation and growth rates of nanocrystals can be further controlled by the reaction temperature, thereby preparing uniformly sized and ultra-small metal ion-doped SnO2 nanocrystals.

[0025] 3. Utilize divalent and trivalent Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+Ions replace tetravalent Sn 4+ ions, achieving P-type doping and then obtaining electron acceptors, which can not only significantly reduce the electron concentration in N-type SnO2 nanocrystals, but also greatly reduce the electron mobility of SnO2 nanocrystals, and achieve a wide range of precise control of the conductivity and mobility of SnO2 nanocrystals;

[0026] 4. Using Mg with widely adjustable electron mobility and conductivity 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystals are used as electron transport layers, combined with organic hole transport layer materials with different hole mobility and conductivity, to achieve a balance of electron and hole transport in quantum dot light-emitting diodes and perovskite thin-film solar cells, thereby improving the performance and stability of these optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The left figure shows that by changing Zn 2+ The electron mobility and conductivity of SnO2 nanocrystals can be precisely controlled by adjusting the ion doping concentration over a wide range. The right figure shows 5% Zn 2+ High-resolution transmission electron microscopy photograph of ion-doped SnO2 nanocrystals, with an average particle size of 3.1nm.

[0028] Figure 2 The left picture shows that by changing Mg 2+ The electron mobility and conductivity of SnO2 nanocrystals can be precisely controlled by adjusting the ion doping concentration over a wide range; the right figure shows 1% Mg 2+ High-resolution transmission electron microscopy photograph of ion-doped SnO2 nanocrystals, with an average particle size of 3.0 nm.

[0029] Figure 3 The left picture shows that by changing Ga 3+ The electron mobility and conductivity of SnO2 nanocrystals can be precisely controlled by adjusting the ion doping concentration over a wide range; the right picture shows 2.5% Ga 3+ High-resolution transmission electron microscopy photograph of ion-doped SnO2 nanocrystals, with an average particle size of 3.1nm.

[0030] Figure 4 The left picture shows that by changing In 3+ The electron mobility and conductivity of SnO2 nanocrystals can be precisely controlled by adjusting the ion doping concentration over a wide range; the right figure shows 7.5% In 3+ High-resolution transmission electron microscopy image of ion-doped SnO2 nanocrystals, with an average particle size of 3.2 nm.

[0031] Figure 5 To utilize different Mg 2+Schematic diagram of the inverted device structure of quantum dot light-emitting diodes prepared by using SnO2 nanocrystals with ion doping and widely adjustable electron mobility as electron transport layers and organic hole transport layers with different hole mobilities.

[0032] Figure 6 To utilize different Zn 2+ Schematic diagram of the structure of a quantum dot light-emitting diode upright device prepared by using SnO2 nanocrystals with ion doping and widely adjustable electron mobility as electron transport layers combined with organic hole transport layers with different hole mobilities.

[0033] Figure 7 To utilize different Ga 2+ Schematic diagram of the upright structure of a perovskite thin-film solar cell device prepared by using ion-doped SnO2 nanocrystals with widely adjustable electron mobility as electron transport layers combined with organic hole transport layers with different hole mobilities.

[0034] Figure 8 To use different 3+ Schematic diagram of the inverted structure of a perovskite thin-film solar cell device prepared by using ion-doped SnO2 nanocrystals with widely adjustable electron mobility as electron transport layers combined with organic hole transport layers with different hole mobilities. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described in detail below with reference to the embodiments.

[0036] Example 1

[0037] Preparation of 5at% Zn by Acetic Acid / Ethanolamine Solution Method 2+ Ion-doped SnO2 nanocrystals:

[0038] First, 0.5 mmol of zinc oxide or zinc acetate or zinc dichloride or zinc nitrate and 9.5 mmol of tin tetrachloride or tin dichloride were added to a 200 ml beaker, 20 ml of acetic acid and 20 ml of ethanolamine were added, and stirred at room temperature to obtain a homogeneous clear solution. Then, the solution was heated to 180 degrees and stirred for 1 hour to obtain 5 at% Zn 2+ Ion-doped SnO2 nanocrystals, with a size of 3.1 nm, can be dispersed in methanol, ethanol or isopropanol. 2+ The doping concentration of ions (0.01-50%) can achieve Zn 2+ The conductivity and mobility of ion-doped SnO2 nanocrystals can be precisely controlled over a wide range, such as Figure 1 shown.

[0039] Example 2

[0040] Preparation of 1 at% Mg by acetic acid / diethanolamine solution method2+ Ion-doped SnO2 nanocrystals:

[0041] First, 0.1 mmol of magnesium acetate or magnesium dichloride or magnesium methoxide and 9.9 mmol of tin tetrachloride or tin dichloride were added to a 200 ml beaker, 50 ml of acetic acid and 50 ml of diethanolamine were added, and stirred at room temperature to obtain a homogeneous clear solution. Then, the solution was heated to 170 degrees and stirred for 2 hours to obtain 1 at% Mg 2+ Ion-doped SnO2 nanocrystals have an average particle size of 3.0 nm and can be dispersed in methanol, ethanol or isopropanol. 2+ The doping concentration of ions (0.01-50%) can achieve Mg 2+ The conductivity and mobility of ion-doped SnO2 nanocrystals can be precisely controlled over a wide range, such as Figure 2 shown.

[0042] Example 3

[0043] Preparation of 2.5 at% Ga by Butyric Acid / Butylamine Solution Method 3+ Ion-doped SnO2 nanocrystals:

[0044] First, 0.25 mmol of gallium acetate or gallium nitrate or gallium trichloride or gallium acetylacetonate and 9.75 mmol of tin tetrachloride or tin dichloride were added to a 200 ml beaker, 20 ml of butyric acid and 20 ml of butylamine were added, and stirred at room temperature to obtain a homogeneous clear solution. Then, the solution was added to a 100 ml autoclave and placed in an oven at 140 degrees for 4 hours. After cooling, 2.5 at% Ga 3+ Ion-doped SnO2 nanocrystals have an average particle size of 3.1 nm and can be dispersed in chloroform. 3+ The doping concentration of ions (0.01-50%) can achieve Ga 3+ The conductivity and mobility of ion-doped SnO2 nanocrystals can be precisely controlled over a wide range, such as Figure 3 shown.

[0045] Example 4

[0046] Preparation of 7.5 at% In by Benzoic Acid / Aniline Solution Method 3+ Ion-doped SnO2 nanocrystals:

[0047] First, 0.75 mmol of indium acetate or indium nitrate or indium trichloride or indium acetylacetonate and 9.25 mmol of tin tetrachloride or tin dichloride were added to a 200 ml beaker, 20 g of benzoic acid and 20 g of aniline were added, the mixed solution was heated to 180 degrees, and reacted for 4 hours under heating and stirring. After cooling, 7.5 at% In was obtained.3+ Ion-doped SnO2 nanocrystals have an average particle size of 3.2 nm and can be dispersed in toluene or chlorobenzene. 3+ The doping concentration of ions (0.01-50%) can achieve In 3+ The conductivity and mobility of ion-doped SnO2 nanocrystals can be precisely controlled over a wide range, such as Figure 4 shown.

[0048] Example 5

[0049] Preparation of 2.5 at% Zn by Acetic Acid / Ethanolamine Solution Method 2+ / 2.5 at% In 3+ Ion co-doped SnO2 nanocrystals:

[0050] First, 0.25 mmol of zinc oxide, zinc acetate, zinc chloride, or zinc nitrate, 0.25 mmol of indium acetate, indium nitrate, indium trichloride, or indium acetylacetonate, and 9.5 mmol of tin tetrachloride or tin dichloride were added to a 200 ml beaker, 30 ml of acetic acid and 30 ml of ethanolamine were added, and stirred at room temperature to obtain a homogeneous clear solution. The solution was then heated to 170 degrees and stirred for 2 hours to obtain 2.5 at% Zn 2+ / 2.5 at% In 3+ Ion co-doped SnO2 nanocrystals, the size of the nanocrystals is 2.8 nm, and they can be dispersed in methanol, ethanol or isopropanol.

[0051] Example 6

[0052] Preparation of 0.5 at% Mg by Butyric Acid / Butylamine Solution Method 2+ / 5.0 at% Ga 3+ Ion co-doped SnO2 nanocrystals:

[0053] First, add 0.05 mmol of magnesium acetate or magnesium methoxide and 0.5 mmol of gallium acetate or gallium nitrate or gallium trichloride or gallium acetylacetonate and 9.45 mmol of tin tetrachloride or tin dichloride into a 200 ml beaker, add 50 ml of butyric acid and 50 ml of butylamine, stir at room temperature to obtain a homogeneous clear solution, then heat the solution to 150 degrees, heat and stir for 4 hours to obtain 0.5 at% Mg 2+ / 5.0 at% Ga 3+ Ion co-doped SnO2 nanocrystals, the size of the nanocrystals is 3.1 nm, and they can be dispersed in chloroform or chlorobenzene.

[0054] Example 7

[0055] This embodiment is the Mg 2+Applications of ion-doped SnO2 nanocrystals as electron transport layers in inverted quantum dot light-emitting diodes include:

[0056] First, different Mg 2+ SnO2 nanocrystals with a wide range of precisely adjustable ion doping concentration, electron mobility and conductivity are dispersed in ethanol at a concentration of about 30 mg / mL. Then, a 40 nm thick electron transport layer film is prepared on an ITO transparent conductive substrate by spin coating. Then, a 15 nm thick quantum dot light-emitting layer film is prepared by spin coating. Then, CBP, TFB, poly-TPD, PTAA, Spiro-OMeTAD or PVK hole transport layer films with different hole mobilities and conductivity are prepared by spin coating with a thickness of about 30 nm. Finally, a 5 nm thick MoO3 hole injection layer and a 100 nm thick metal aluminum electrode are deposited in sequence by vacuum thermal evaporation to complete the preparation of the quantum dot light-emitting diode inverted device. After testing, the external quantum efficiency of the device is 20.1%. According to the different hole mobilities of the organic hole transport material, different Mg 2+ The device structure of the inverted quantum dot light emitting diode is shown in Figure 2. Figure 5 shown.

[0057] Example 8

[0058] This embodiment is the Zn 2+ The application of ion-doped SnO2 nanocrystals as electron transport layer in upright quantum dot light-emitting diodes includes:

[0059] First, a 30 nm thick PEDOT:PSS hole injection layer was prepared on an ITO transparent conductive substrate by spin coating. Then, a CBP, TFB, poly-TPD, PTAA, Spiro-OMeTAD or PVK hole transport layer film with a thickness of about 30 nm was prepared by spin coating with different hole mobility and conductivity. Then, a 15 nm thick quantum dot light-emitting layer film was prepared by spin coating as the light-emitting layer. According to the different hole mobility of the organic hole transport material, different Zn 2+ SnO2 nanocrystals with ion doping concentrations of about 30 mg / mL were dispersed in ethanol. A 40 nm thick SnO2 nanocrystal electron transport layer with different electron mobilities was prepared on the quantum dot light-emitting layer by spin coating. Finally, a 100 nm thick metal aluminum electrode was deposited by thermal evaporation to complete the preparation of the upright quantum dot light-emitting diode device. The device structure of the upright quantum dot light-emitting diode is shown in FIG. Figure 6As shown in the figure, the external quantum efficiency of the tested device is 24.4%, the maximum brightness of the red light device exceeds 200,000 nits, and there is no observed positive aging effect of the device, that is, the phenomenon that the external quantum efficiency increases after the device is placed for a period of time. 2+ The SnO2 nanocrystal electron transport layer with different ion doping concentrations and electron mobilities achieves a balanced transport of electrons and holes in the device.

[0060] Example 9

[0061] This embodiment is the Ga 3+ Applications of ion-doped SnO2 nanocrystals as electron transport layers in inverted perovskite thin-film solar cells include:

[0062] use Figure 7 The device structure shown in the figure is used to prepare the inverted perovskite thin film solar cell. ITO or FTO transparent conductive glass is used as the substrate. First, different Ga 3+ SnO2 nanocrystals with a wide range of precisely adjustable ion doping concentration, electron mobility and conductivity were dispersed in ethanol at a concentration of about 30 mg / mL and 40 nm thick films with different GaN content were prepared on TIO or FTO substrates by spin coating. 3+ The SnO2 nanocrystal electron transport layer with different ion doping concentrations and electron mobility is then spin-coated to prepare a 350 nm thick perovskite light absorption layer film, followed by spin-coating of an undoped CBP, TFB, poly-TPD, PTAA, Spiro-OMeTAD or PVK hole transport layer film with a thickness of about 30 nm. Finally, a 5 nm thick MoO3 hole extraction layer and a 100 nm thick gold electrode are evaporated to complete the preparation of the positive perovskite thin film battery. After testing, the photoelectric conversion efficiency of the device reaches more than 24%. According to the different mobility and conductivity of the hole transport layer material, different Ga 3+ The SnO2 nanocrystal electron transport layer with adjustable ion doping concentration and electron mobility achieves the transport balance of electrons and holes in the device.

[0063] Example 10

[0064] This embodiment is the invention of In 3+ Applications of ion-doped SnO2 nanocrystals as electron transport layers in inverted perovskite thin-film solar cells include:

[0065] use Figure 8The device structure shown is used to prepare an inverted perovskite thin-film solar cell. ITO or FTO transparent conductive glass is used as the substrate, and a 30 nm thick PEDOT:PSS hole injection layer is spin-coated on it. Then, CBP, TFB, poly-TPD, PTAA, Spiro-OMeTAD or PVK hole transport layer films with different hole mobility and conductivity are spin-coated to a thickness of about 30 nm. Then, a 350 nm thick perovskite light absorption layer film is spin-coated. Finally, different In layers are added according to the different hole mobility of the organic hole transport material. 3+ SnO2 nanocrystal chlorobenzene dispersions with different ion doping concentrations, electron mobility and conductivity were spin-coated on the perovskite light absorbing layer (concentration of about 30 mg / mL) to form a 40 nm thick film with different In 3+ The SnO2 nanocrystal electron transport layer with different ion doping concentrations and electron mobility was finally deposited with a 100 nm thick metal aluminum electrode by thermal evaporation to complete the preparation of the inverted perovskite thin film solar cell device. After testing, the average photoelectric conversion efficiency of the device reached 25.4%. According to the different hole mobility and conductivity of the hole transport layer material, different In 3+ The SnO2 nanocrystal electron transport layer with different ion doping concentrations and electron mobilities achieves a balanced transport of electrons and holes in the device.

[0066] The above examples are only used to help understand the method and core concept of the present invention. It should be pointed out that for those skilled in the art, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. For example, by using P-type Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ SnO2 nanocrystals with widely adjustable electron mobility and conductivity prepared by ion doping are used as electron transport layers, and are combined with organic hole transport layer materials with different hole mobilities and conductivities. They can all be used to prepare inverted and upright quantum dot light-emitting diodes and perovskite thin-film solar cells, without being limited by the above specific embodiments.

Claims

1. A method for precisely controlling the electron mobility and conductivity of SnO2 nanocrystals over a large range by P-type doping, characterized in that: The following steps are involved: (1) Using organic acids and organic amines as organic ligands to control the nucleation and growth rates of SnO2 nanocrystals; (2) Using organic acids and organic amines to gradually release water at high temperatures, catalyzing and promoting the gradual hydrolysis of tin tetrachloride or tin dichloride to form SnO2 nanocrystals; (3) Add Mg to the reaction precursor solution 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion precursor, Mg is prepared by high temperature reaction 2+ 、Zn 2 + 、Ga 3+ 、In 3+ Ion P-type doped SnO2 nanocrystals can achieve precise control of the conductivity and electron mobility of SnO2 nanocrystals over a wide range by changing the concentration of doped metal ions; (4) Prepared alcohol-soluble or oil-soluble Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystals are dispersed in water, ethanol, toluene or toluene, and MgO is prepared by solution film forming methods such as spin coating, inkjet printing, screen printing, slit spraying, Czochralski method, and doctor blade coating. 2+ 、Zn 2+ 、Ga 3+ 、In 3+ SnO2 nanocrystalline films with p-type ion doping and precise tunable electron mobility and conductivity over a wide range; (5) Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystalline films with precisely adjustable conductivity and electron mobility over a wide range are used as electron transport layers, and are paired with organic hole transport layers with different hole mobilities and conductivities. They are applied to optoelectronic devices such as quantum dot light-emitting diodes and perovskite thin-film solar cells to achieve a balanced transport of electrons and holes, thereby improving the performance and stability of these semiconductor optoelectronic devices.

2. The method according to claim 1, characterized in that The organic acid and organic amine at least include one or more of the following organic acids and organic amines, organic acids or organic amines with a carbon chain length ranging from 1 carbon to 18 carbons, and the organic acids are formic acid, acetic acid, propionic acid, acrylic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, isooctanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, stearic acid, oleic acid, linoleic acid, benzoic acid, phenylphosphoric acid, benzenesulfonic acid, citric acid, ascorbic acid, ethylenediaminetetraacetic acid, glycolic acid, oxalic acid, gluconic acid, lactic acid, acrylic acid, salicylic acid, tartaric acid, taurine, glycine, One or more of glutamic acid, polyacrylic acid, and polylactic acid; the organic amine is one or more of methylamine, ethylamine, propylamine, butylamine, tert-butylamine, pentylamine, hexylamine, heptylamine, octylamine, isooctylamine, decylamine, dodecylamine, tetradecylamine, octadecylamine, oleylamine, aniline, benzylamine, ethanolamine, diethanolamine, triethanolamine, dibutylamine, diethylamine, pyridine, propanolamine, isopropanolamine, diisopropanolamine, 2-amino-1-butanol, 2-amino-1,3-propylene glycol, 2-amino-2-methyl-1-propanol, diglycolamine, and polyethyleneimine.

3. The method according to claim 1, characterized in that The high temperature reaction includes 30 degrees to 300 degrees, and the heating methods include normal pressure heating and high pressure autoclave heating.

4. The method according to claim 1, wherein The P-type doping ions include but are not limited to Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ One or more of the ions, with a molar doping concentration ranging from 0.01-50%.

5. The method according to claim 1, characterized in that The solution film forming method includes spin coating, inkjet printing, screen printing, slit spraying, pulling method and blade coating method.

6. The method according to claim 1, characterized in that The field of optoelectronic devices includes, but is not limited to, quantum dot light emitting diodes and perovskite thin film solar cells, including upright and inverted device structures.

7. Mg prepared by the method according to any one of claims 1 to 6 2+ 、Zn 2+ 、Ga 3+ 、In 3+ The ion-doped SnO2 nanocrystalline film is characterized by: The electron mobility and conductivity of the nanocrystalline film can be precisely controlled over a wide range by changing the concentration of doped metal ions. -3 S cm -1 to 10 -8 S cm -1 , the electron mobility of SnO2 nanocrystalline film increases from 10 -2 cm 2 V -1 s -1 to 10 -6 cm 2 V -1 s -1 Precisely adjustable within a wide range.

8. A photoelectric device, characterized in that: Including the Mg according to claim 7 2+ 、Zn 2+ 、Ga 3+ 、In 3+ An ion-p-type doped SnO2 nanocrystalline film is used as an electron transport layer, and an organic hole transport layer material with different hole mobility and conductivity is used in combination with it. The optoelectronic device is a quantum dot light-emitting diode or a perovskite thin-film solar cell; The photoelectric device is a quantum dot light emitting diode, and its device structure includes an ITO transparent conductive substrate, an electron transport layer, a quantum dot light emitting layer and a hole transport layer.

9. The optoelectronic device according to claim 8, characterized in that The photoelectric device is a perovskite thin film solar cell, and its device structure includes an ITO or FTO transparent conductive glass substrate, an electron transport layer, a perovskite light absorption layer and a hole transport layer.

10. An application of precisely controlling the electron mobility and conductivity of SnO2 nanocrystals over a wide range by P-type doping, characterized in that: The Mg according to claim 7 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystalline films are used as electron transport layers in optoelectronic devices such as quantum dot light-emitting diodes and perovskite thin-film solar cells. Organic hole transport materials with different hole mobility and conductivity, such as 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt(4,4'-(N-(4-butylphenyl))] (TFB), poly[bis(4-butyl)-bis(phenyl)benzidine] (poly-TPD), polytriarylamine (PTAA), 2,2',7,7'-tetrakis(N,N-di-p-methoxyaniline)-9,9'-spirobifluorene (Spiro-OMeTAD), and poly(9-vinylcarbazole) (PVK), have hole mobilities ranging from 10 -4 to 10 -6 cm 2 V -1 s -1 Decrease in sequence and choose to match different electron mobility Mg 2+ 、Zn 2+ 、Ga 3+ 、In 3+ Ion-doped SnO2 nanocrystalline films serve as electron transport layers, achieving a balanced transport of electrons and holes, thereby improving the performance and stability of these semiconductor optoelectronic devices.